Data processing of non-stationary capillary viscometer for blood - V. G. Leshchenko; M. V. Goltsev; D. V. Mansurov; V. A. Mansurov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The work is devoted to the development of the theoretical foundations of the processing of measurement results and the algorithm for processing the results for automating measurements for a non-stationary capillary viscometer. The proposed algorithm allows achieving measurement performance and obtaining hemorheological data for diagnostic purposes with a satisfactory degree of accuracy. The results obtained with use of non-stationary capillary viscometer are compared with results achieved with use of rotational viscometer.